2019
DOI: 10.1371/journal.pone.0213448
|View full text |Cite
|
Sign up to set email alerts
|

Food security and food self-sufficiency around the world: A typology of countries

Abstract: The particularities of agriculture, as a sector which ensures food supply, result from many factors, including the multilateral interaction between the environment and human activity. The extent of human intervention in the food production process is usually measured with the amount of capital expenditure. Therefore, the food production potential and the resulting food security depend on both natural and economic factors. This paper identifies the current status of food security in different countries around t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 42 publications
(32 reference statements)
4
33
0
1
Order By: Relevance
“…This could be due to either funding deficiencies hindering dynamics (low income countries) or consolidation of relative importance of research disciplines for high-income countries and rigidities to modify the status quo (e.g., politics around budgets and departmental expansions); and (6) disciplines such as Psychology and Arts are over-weighted (in relative terms) in high-income countries, while disciplines such as Agriculture and Immunology are more relevant and remain over-weighted for low-income countries. This is reflective of the different concerns that wealthier countries face (mental health, leisure) versus those of lower income countries (food security, survival) [28]. Diminishing interdisciplinary relations, such as those mentioned regarding Economics and Business, can be concerning given the need to tackle ever more complex problems [29].…”
Section: Plos Onementioning
confidence: 99%
“…This could be due to either funding deficiencies hindering dynamics (low income countries) or consolidation of relative importance of research disciplines for high-income countries and rigidities to modify the status quo (e.g., politics around budgets and departmental expansions); and (6) disciplines such as Psychology and Arts are over-weighted (in relative terms) in high-income countries, while disciplines such as Agriculture and Immunology are more relevant and remain over-weighted for low-income countries. This is reflective of the different concerns that wealthier countries face (mental health, leisure) versus those of lower income countries (food security, survival) [28]. Diminishing interdisciplinary relations, such as those mentioned regarding Economics and Business, can be concerning given the need to tackle ever more complex problems [29].…”
Section: Plos Onementioning
confidence: 99%
“…Considering the methodology section, it is necessary to remember that the goal of this search was to identify patterns and the use of tools, particularly from the perspective of system science, in problems related to food sustainability and urban agriculture. Although the literature review did not focus exclusively on urban agriculture, the algorithm for community detection and its subsequent review indicated that the works that deal with urban agriculture as their central theme with a precise geographical context did not identify particularities in the spaces, techniques, forms of management, and organizational structures for food production in urban areas [10,19,28,54,105,106].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ward et al [11] suggested using linear programming to evaluate diet styles and determine the feasibility of urban agriculture modalities. However, Baer-Nawrocka and Sadowski [28] indicated that one of the factors that influences problems related to food self-sufficiency is the high concentration of the agricultural sector in related studies. Additionally, Montiel [29] considered another limitation as the attempts to understand the different factors in isolation and the low potential to handle multiple social and ecological interactions at the local, regional, and international levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Зарубежные исследователи связывают продовольственную безопасность с такими показателями, как наличие запасов и стабильность производства продовольствия, физическая и экономическая доступность продовольствия, содержание в нем пищевых веществ [Bach et al, 2014;Baer-Nawrocka et al, 2019;Measuring..., 2019].…”
Section: таблица 1 состав показателей действующей доктрины продовольсunclassified